2013
DOI: 10.1189/jlb.0812396
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids PKA-dependently induce a switch of the IL-10/IL-12 ratio and reduce proinflammatory capability of human macrophages

Abstract: That cholestatic conditions are accompanied by an enhanced susceptibility to bacterial infection in human and animal models is a known phenomenon. This correlates with the observation that bile acids have suppressive effects on cells of innate and adaptive immunity. The present study provides evidence that in human macrophages, bile acids inhibit the LPS-induced expression of proinflammatory cytokines without affecting the expression of the anti-inflammatory cytokine IL-10. This results in a macrophage phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 34 publications
6
119
2
1
Order By: Relevance
“…As the b-ZIP domain of LAP has been reported to interact with the Rel homology domain of NF-κB and to enhance NF-κB-dependent transcription (82)(83)(84)(85), the dominant-negative C/EBPβ isoform LIP could also blunt NF-κB activation and further decrease the inflammatory response. Several studies demonstrate that TGR5 activation inhibits NF-κB signaling through pleiotropic mechanisms, including IκBα, CREB, and c-Fos phosphorylation (32,34,36). Our present data add modulation of LIP translation to the means by which TGR5 could reduce the inflammatory actions of NF-κB.…”
Section: Tgr5mentioning
confidence: 63%
See 1 more Smart Citation
“…As the b-ZIP domain of LAP has been reported to interact with the Rel homology domain of NF-κB and to enhance NF-κB-dependent transcription (82)(83)(84)(85), the dominant-negative C/EBPβ isoform LIP could also blunt NF-κB activation and further decrease the inflammatory response. Several studies demonstrate that TGR5 activation inhibits NF-κB signaling through pleiotropic mechanisms, including IκBα, CREB, and c-Fos phosphorylation (32,34,36). Our present data add modulation of LIP translation to the means by which TGR5 could reduce the inflammatory actions of NF-κB.…”
Section: Tgr5mentioning
confidence: 63%
“…TGR5 is also expressed in cells of the hematopoietic system, such as monocytes and macrophages, and confers potent antiinflammatory properties in vitro and in vivo (31)(32)(33)(34)(35)(36). Recent work from our laboratory revealed that the immune-suppressive actions of TGR5 in macrophages contribute to the prevention of the atherosclerotic process (34).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, effects in dog occurred at concentrations overlapping with the IC 50 values for inhibition of human TNF-a and IL-12p40 production (in vitro functional indices of efficacy) and, for BIX02694, at near-therapeutic concentrations in a preclinical DNBS efficacy model suggesting an inability to separate GPBAR1-mediated efficacy and ontarget cardiovascular liabilities in vivo and that resulted in termination of the project. GPBAR1 signaling in myeloid cells leads to downregulation of responses to proinflammatory stimuli in primary human macrophages in vitro (Haselow et al, 2013;Yoneno et al, 2013) and reductions in inflammation in vivo via genetic approaches in which knockout mice are more susceptible to inflammation (Wang et al, 2011), including injury-induced colitis (Cipriani et al, 2011), or in which receptor agonists offer protection from colitis and other inflammatory models (Martín et al, 2010;Cipriani et al, 2011;Pols et al, 2011a). In colitis, the improvement in the clinical score appears to be linked to a direct impact on monocyte infiltration into the colon, consistent with the importance of these cells in disease pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal and hepatotrophic viruses replicate in the presence of bile acids that influence cellular signaling, innate and adaptive immune responses (22,29,30), and interferon (IFN) signaling (31). Hepatitis C virus (HCV) and hepatitis B virus (HBV) benefit from bile acid-dependent FXR activation (32,33), while for rotaviruses a significantly reduced fecal shedding was shown at 1 and 3 days postinfection in chenodeoxycholic acid-fed mice (34).…”
mentioning
confidence: 99%